Perancangan Interior Auditorium di Surabaya - Sulistio, Riyanto (Intra, 2013)
Auditorium project in Surabaya is engaged in the arts, particularly the art of music. facilities planned include a standardized auditorium, backstage, and do not forget the cafe shop. Art music favored by many people from the young to the elderly with a wide range of music. So the theme of this design refers to the complex nature and can not be guessed that the theme of